Strategi Corporate Social Responsibility Dompet Dhuafa dalam Membangun Brand Differentiation Lembaga - Pranawukir, Iswahyu; Sukma, Agus Hitopa (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
The research aims to determine the Dompet Dhuafa Foundation's CSR strategy in building brand differentiation through the establishment of the Smart Ekselensia Republika school. It also concerns the dynamics of the Dompet Dhuafa Foundation's business paradigm which focuses on CSR programs to form brand differentiation. This type of research is case study with a qualitative descriptive method. It aims to describe the establishment of a school accompanied by an explanation of the process of occurrence, development and changes in various aspects of the dynamics of its CSR. Thus, there are peculiarities of cases which the researcher describes descriptively based on dynamic and contextual chronology. The results showed that the Dompet Dhuafa Foundation's CSR strategy in building brand differentiation is based on social awareness, that business contributions are social benefits; economic awareness, that the maximum profit from business is the maximum benefit in increasing charity in society; and legal awareness, that justice efforts that have been criticized by the pudblic can be maximally fulfilled because the efforts being carried out have a segment of the dhuafa. Differentiation is an achievement that combines the shared value business context in the three intelligences. Intellectual intelligence is proven in the provision of education, emotional intelligence by building social service businesses for the poor, as well as spiritual intelligence with the principles of trust, worship and Islam. So, business differentiation is a business that presents God in its operations.